(untitled) (AYUSHDHARA, 2020)
Inspite of a highly rational and inventively developed brain, mankind is ultimately a mortal race of creatures. It has been disturbed every now and then with sudden and severe ravages of various diseases which require different remedies ranging from mere witchcrafts to the intake of certain rubbish things.